Exploring the Information Requirements of Poultry Farmers in Namakkal: A Comprehensive Study - Pushpam, P.; Jayaprakash, M.; Adamu, Alhassan (Journal of Information and Knowledge, 2025)
In Namakkal, Tamil Nadu, poultry farming plays a crucial role in the local economy by creating jobs and revenue streams. However, because of infrastructure constraints, farmers face difficulties obtaining relevant information. This study aims to determine the information requirements, sources, difficulties, and favoured means of communication among Namakkal poultry producers (Folitse et al., 2018; Gopalasundar, 2021). One hundred fifty-five poultry producers participated in focus groups and in-person interviews to gather data. Data analysis was done using Radial Basis Function and Factor Analysis, which were made possible by SPSS software. Government laws, market trends, nutrition, and poultry health are among poultry farmers’ most important information needs (Malarvizhi & Geetha, 2015; Ovharhe et al., 2021). Farmers actively seek knowledge from various sources, including agricultural journals, local farmer networks, and online research, despite obstacles, including inadequate infrastructure (Folitse et al., 2018; Tikwe et al., 2015).In order to meet the unique demands of poultry farmers in Namakkal, this study emphasizes the significance of customized information distribution strategies. Stakeholders can enable poultry farmers to make better decisions, increase productivity, and support the long-term viability of the poultry sector in the area by improving information distribution through readily available platforms (Ovharhe et al., 2021; Esnaola-Gonzalez et al., 2020).